1985
DOI: 10.1021/jm00381a014
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors. I. Structural modification of 5-substituted 3,5-dihydroxypentanoic acids and their lactone derivatives

Abstract: A series of 5-substituted 3,5-dihydroxypentanoic acids and their derivatives have been prepared and tested for inhibition of HMG-CoA reductase in vitro. In general, unless a carboxylate anion can be formed and the hydroxy groups remain unsubstituted in an erythro relationship, inhibitory activity is greatly reduced. Furthermore, only one enantiomer of the ring-opened form of lactone 6a(+/-) possesses the activity displayed by the racemate. Insertion of a bridging unit other than ethyl or (E)-ethenyl between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(29 citation statements)
references
References 2 publications
1
27
0
1
Order By: Relevance
“…4, 14. 15]: lovastatin [16], pravastatin [17], simvastatin [18], and fluvastatin [19], A number of clinical studies have demonstrated that HMG-CoA re ductase inhibitors (statins), either alone or in association with other hypolipidemic drugs, can induce regression of vascular atherosclerosis [9][10][11]. decrease the incidence of coronary artery disease [9,10], and improve survival in patients with coronary artery disease [8],…”
Section: Introductionmentioning
confidence: 99%
“…4, 14. 15]: lovastatin [16], pravastatin [17], simvastatin [18], and fluvastatin [19], A number of clinical studies have demonstrated that HMG-CoA re ductase inhibitors (statins), either alone or in association with other hypolipidemic drugs, can induce regression of vascular atherosclerosis [9][10][11]. decrease the incidence of coronary artery disease [9,10], and improve survival in patients with coronary artery disease [8],…”
Section: Introductionmentioning
confidence: 99%
“…From the structural prospective, these natural and semisynthetic statins are chiral 3,5-dihydroxyheptanoic acids that bind at C-7 to the substituted chiral unsaturated decalin core. The 3,5-dihydroxyheptanoic acid structural motif has been shown to be responsible for the pharmacological activity of statins [8].…”
Section: Discovery Of Statinsmentioning
confidence: 99%
“…The insertion of a bridging unit other than ethyl or an (E)-ethenyl between the 5-carbinol moiety and an appropriate lipophilic moiety attenuates the activity. Other derivatives which have different inhibition activities help to determine the essentiality of the functional group [47]. Fig.…”
Section: Fig (2b)mentioning
confidence: 99%
“…3A) shows better inhibition activity (IC 50 = 22 M) of HMG-CoA reductase among a series of 5-substituted 3,5-dihydroxypentanoic acids and their derivatives in in vitro condition. It has been reported that the insertion of a bridging unit other than ethyl or (E)-ethenyl between 2,4-dichlorophenyl and 5-carbinol moiety had decreased the activity [47].…”
Section: Origin and Routes Of Synthesis Of Hypo-cholesterolemic Compomentioning
confidence: 99%